Impact of Intermediate-Task Training on Few-Shot Cross-Lingual Transfer Performance in XTREME-R - Assignee Research (Assignee Research, 2026)
Intermediate-task training—fine-tuning a pretrained model on an intermediate task before fine-tuning again on the target task—often improves model performance substantially on language understanding tasks in monolingual English settings. We investigate whether English intermediate-task training is still helpful on non-English target tasks. Using nine intermediate language-understanding tasks, we evaluate intermediate-task transfer in a zero-shot cross-lingual setting on the XTREME benchmark. We
Machine-generated literature synthesis.